A blinded, randomized, placebo‐controlled trial of the efficacy and safety of the Janus kinase inhibitor oclacitinib (Apoquel®) in client‐owned dogs with atopic dermatitis. Issue 6 (December 2013) - Cosgrove, Sallie B.; Wren, Jody A.; Cleaver, Dawn M.; Walsh, Kelly F.; Follis, Stacey I.; King, Vickie I.; Tena, Jezaniah‐Kira S.; Stegemann, Michael R.
<x xml:space="preserve">Abstract</x> Background Pruritus is the hallmark clinical sign of atopic dermatitis (AD) in dogs. Preliminary study results suggest that oclacitinib, a selective Janus kinase inhibitor, could reduce pruritus and associated inflammatory skin lesions in dogs with AD. Hypothesis/Objectives The objective was to evaluate efficacy and safety of oclacitinib (Apoquel®) for the control of AD in a randomized, double‐blind, placebo‐controlled trial. Animals Clinicians at 18 specialty clinics enrolled client‐owned dogs (n = 299) with a history of chronic AD. Methods Dogs were randomized to receive either oclacitinib (0.4–0.6 mg/kg twice daily for 14 days and then once daily for up to 112 days) or an excipient‐matched placebo. Owners assessed visual analog scale (VAS) scores of pruritus on days 0, 1, 2, 7, 14, 28, 56, 84 and 112. Clinicians assessed Canine AD Extent and Severity Index (CADESI‐02) scores on days 0, 14, 28, 56, 84 and 112. Results On days 1, 2, 7, 14 and 28, oclacitinib‐treated dogs had a 29.5, 42.3, 61.5, 66.7 and 47.4% reduction from baseline in owner‐assessed pruritus scores, respectively, compared with a 6.5, 9.1, 6.5, 3.9 and 10.4% reduction in placebo‐treated dogs. On days 14 and 28, dermatologists recorded a 48.4% reduction in CADESI‐02 scores in oclacitinib‐treated dogs compared with a 1.7% reduction and a 3.6% increase in placebo‐treated dogs. After day 28, >86% of all placebo‐treated dogs had moved to an open‐label study, making between‐group comparisons biased. Differences were significant at all time points assessed (P < 0.0001). Conclusions and clinical importance Oclacitinib provided rapid, effective and safe control of AD, with substantial improvement in VAS and CADESI‐02 scores.